Mind and Map Method: Upaya Meningkatkan Keterampilan Menulis Teks Deskripsi pada Siswa MTs Negeri 4 Bantul - Suratmi (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
This research aims to improve the writing ability of text descriptions through learning by using the mind and map method in 25 students of the VII-F MTs Negeri 4 Bantul Semester in the year of the 2019/2020 course. The study uses class action methods, consisting of two cycles covering the planning, implementation, observation, and reflection stages. Data collection techniques using writing tests, observations, field records and photo documentation. The results showed that learning with the mind map method can improve the activity and skills of students writing the description text, both in terms of process and product. It is demonstrated by the enhancement of students in intensified student interest, kekondusifan the photo observation process to create mind map, student intensified in doing independent task, kekondusifan students when a student is presenting, and kekondusifan students during reflection activities. Quality improvement of the process positively impacts the product quality improvement. It is seen in the test results writing the description text from the pre-action stage until cycle 2 increased by a pre-action of 52%, I cycle 76%, and cycle II 96%. The mind map method is one of the learning method of writing that is able to improve the activity and skills of the student writing the description text.